Role of education towards environmental management: Case study Goma Junior High School DR Congo - Dechy, Bernard; Chinyhabuuma, Mwisha (JIPSINDO, 2021)
Research aims to understand the rule of education in Goma Junior High School, to understand the level of environmental management, and relationship between education and environmental management. This research employed a mixed method which is quantitate and qualitative. Technique to gather non-numerical data, the researcher utilized a qualitative data collection approach. The results show that environmental education helps students improve their living, study through tree planting, waste management, good environmental management in the school farm and increase number of environmental management ambassadors in the community. The students have a moderate level of understanding on environmental issues and concerns while the rest of the students either have very good or good in understanding environmental management issues. Moreover, students are at the knowledge and understanding A to A continuum level while the list is in the problem-solving skills level of the A to A continuum phase. Students become more responsible in matters dealing with environmental management such as planting tree, keeping their living environment clean and attractive, and managing waste well. Peranan pendidikan terhadap menejemen lingkungan: Studi kasus Goma Junior High School DR Congo Penelitian ini bertujuan untuk mengetahui bagaimanakah aturan pendidikan di Sekolah Menengah Pertama Goma, untuk memahami sistem pengelolaan lingkungan, dan memahami hubungan antara pendidikan dan pengelolaan lingkungan di Sekolah Menengah Pertama Goma, DR Congo. Penelitian ini menggunakan metode campuran yaitu kuantitatif dan kualitatif. Pengumpulan data nonnumerik menggunakan pendekatan pengumpulan data kualitatif. Hasil penelitian menunjukkan bahwa pendidikan lingkungan membantu siswa meningkatkan taraf hidup, belajar melalui penanaman pohon, pengelolaan sampah, pengelolaan lingkungan yang baik di sekolah pertanian dan meningkatkan jumlah duta pengelolaan lingkungan di masyarakat. Sebagian besar siswa memiliki tingkat pemahaman yang moderat tentang masalah dan masalah lingkungan, sedangkan siswa lainnya memiliki pemahaman yang sangat baik atau baik dalam masalah pengelolaan lingkungan. Siswa berada pada pengetahuan dan pemahaman tingkat kontinum A ke A sedangkan daftar berada pada tingkat keterampilan pemecahan masalah dari tahap kontinum A ke A. Mahasiswa menjadi lebih bertanggung jawab dalam hal-hal yang berhubungan dengan pengelolaan lingkungan seperti penanaman pohon, menjaga lingkungan hidup tetap bersih dan menarik, serta mengelola sampah dengan baik.